Cervical musculoskeletal dysfunction in headache: How should it be defined? - Jull, G.; Hall, Toby (2018)
Neck pain commonly accompanies migraine and tension-type headache, but the literature is divided on whether this neck pain is a headache symptom or is associated with cervical musculoskeletal dysfunction. Clarification is essential for hypotheses on the pathogenesis of these headaches and their variants and for decisions on suitability of local neck treatments, both from research and clinical practice perspectives. Reasons for disparate findings could relate to participant selection in headache studies and/or the bases on which decisions on the presence of cervical musculoskeletal dysfunction are reached. Propositions towards gaining a clearer picture of migraine and tension-type headache related neck pain include first, stricter inclusion criteria and reporting of headache characteristics of study participants. Second, reliance on pain sensitivity or the presence of neck tenderness/trigger points as measures be discarded, as they are not uniquely tied to a musculoskeletal disorder. Instead, place reliance on tests of musculoskeletal (dys)function. Third, the values and interpretation of single measures or tests of impairment/dysfunctions can be non-informative and do not reflect the presentation of cervical musculoskeletal disorders. Rather, a typical presentation includes at a fundamental level, interrelated changes in cervical movement, segmental joint and muscle function. We advocate that these measures be adopted as the core set of related measures to define cervical musculoskeletal dysfunction in headache. This does not deter inclusion of other measures of interest or qualification.